2019
DOI: 10.1080/01442872.2019.1599839
|View full text |Cite
|
Sign up to set email alerts
|

Positioning the ageing subject: articulations of choice in Swedish and UK health and social care

Abstract: What happens when similar measures are being introduced in different national contexts? This article studies the ways in which patient choice has been articulated in public and official reports on health care in the two contexts of Sweden and the UK, whose welfare systems are typically comprehended as different. Specific interest is directed towards the construction of patient positions, and policy documents are analyzed using discourse theory. The results show many similarities between the national contexts; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 66 publications
1
11
0
3
Order By: Relevance
“…Our findings also align with the results of interview and policy studies that analyse how the choice discourse (connected with a market discourse) legitimises certain ways forward in Swedish social care (e.g. Nilsson et al, 2018;Lindberg and Lundgren, 2019). Elder-care is the subject of renewed public attention in the context of the COVID-19 pandemic and it is important to explore the way home care is being framed.…”
Section: Concluding Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our findings also align with the results of interview and policy studies that analyse how the choice discourse (connected with a market discourse) legitimises certain ways forward in Swedish social care (e.g. Nilsson et al, 2018;Lindberg and Lundgren, 2019). Elder-care is the subject of renewed public attention in the context of the COVID-19 pandemic and it is important to explore the way home care is being framed.…”
Section: Concluding Discussionsupporting
confidence: 78%
“…This approach problematises the understandingunderpinning much care researchof home care as a given entity. Previous studies have shown how discourses on choice, marketisation and NPM shape health and social care in Sweden and other Nordic countries (Andersson and Kvist, 2015;Vabø, 2015;Burau et al, 2016;Nilsson et al, 2018;Lindberg and Lundgren, 2019). However, studies have not yet analysed the discursive struggles involved in the formation of home care as an institution in the context of the implementation of choice.…”
Section: Research On Social Care and Choice Systems In Nordic Contextsmentioning
confidence: 99%
“…GPs' paradoxical position-at the interface of both the public and the expert systems in charge of vaccination, placing them simultaneously within and outside of this system-is also evident in the individualist approach of healthcare introduced through neoliberal reforms in the West in the 1990s (Lindberg & Lundgren, 2019). Healthcare was personalized to meet the needs and desires of individuals, which of course has very positive aspects.…”
Section: Article Historymentioning
confidence: 99%
“…Det finns även forskning som ligger utanför digitaliseringen av vården som i sammanhanget är relevant. Studier av vårdpolicy visar hur en nyliberal logik som bland annat innebär ökad privatisering och stora för-hoppningar på kostnadseffektivisering genom konkurrens präglar organiseringen av vården (Andersson & Kvist 2015;Lindberg & Lundgren 2018). I detta systemskifte, som i Sverige har pågått sedan början av 1990-talet, har valfrihet setts som ett ledord och marknadifiering av vård och omsorg har skrivits fram som någonting som ska stärka individen genom att de själva fritt kan välja vårdgivare (Andersson & Kvist 2015;Dahlgren 2018).…”
Section: Tidigare Forskningunclassified
“…När vissa av debattörerna talar om att vårdföretag inte ska sälja vård likt andra varor på en marknad, kan man se det som ett uttryck för en kritik mot konsumtionssamhället (Bauman 2008) och mot det nyliberala systemskifte som andra forskare menar kommit att karaktärisera svensk vårdpolicy (Andersson & Kvist 2015;Lindberg & Lundgren 2018;Dahlgren 2018). Den typ av avreglering av offentlig sektor som gestaltas i materialet som här undersökts, där "konsultföretag och teknikföretag gräver guld", är ofta mycket ingående, menar Bauman, samtidigt som den privata sektorn får fortsatt statligt stöd.…”
Section: Slutsatserunclassified